REINFORCEMENT OF THE MYTH OF MANGUNI IN MINAHASAN COMMUNITY, NORTH SULAWESI - Rinny Liando, Mayske (E-Journal of Cultural Studies, 2014)
Oral traditions may be found in many regions. One of them which enriches the treasure of local culture is the oral tradition of the myth of manguni (owl), which, in Minahasa, North Sulawesi, is purified and constitutes part of the local traditions which may help the local people overcome their problems. The oral tradition of the myth of manguni constitutes one of the local cultural products which may be potentially created, as can be seen in the creative industries currently motivated by the government of Indonesia. This present study was particularly intended to identify the form, ideology, and implication of the reinforcement of the myth of manguni in the community of Minahasa, North Sulawesi.   The result of the present study showed that the myth of manguni was reinforced by the community in Minahasa, North Sulawesi, not only in the form of the creative industry of souvenirs, which are highly economically valuable, but also in various forms of symbols. The reinforcement of the myth of manguni in the community of Minahasa, North Sulawesi, contained the ideology of heroism, the myth of the origin of Minahasa, amusement, the communication between human beings and the Creator, conservation, and commodification. The implication of the reinforcement of the myth of manguni in the community of Minahasa, North Sulawesi, on the socio-culture of the Minahasan people included the aspect of ideological superstructure, the aspect of socio-culture and the aspect of material infrastructure.